2017
DOI: 10.1002/2017ja024341
|View full text |Cite
|
Sign up to set email alerts
|

Observations and Simulations of Eddy Diffusion and Tidal Effects on the Semiannual Oscillation in the Ionosphere

Abstract: We use the National Center for Atmospheric Research TIEGCM (Thermosphere Ionosphere Electrodynamics General Circulation Model) model to investigate the eddy diffusion and tidal effects on the ionosphere SAO (semiannual oscillation). We also use the COSMIC (Constellation Observing System for Meteorology, Ionosphere, and Climate) satellite GPS radio occultation observations to validate the simulation results. The TIEGCM is driven at the 97 km lower boundary by tidal and gravity wave (eddy diffusion coefficient) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The lower atmosphere can also contribute to the latitudinal dependency of the summer‐to‐winter difference in ∑ O/N 2 . Seasonal and latitudinal variations in wave/tidal activity, turbulent mixing, and residual circulations in the mesosphere and lower thermosphere region strongly impact the seasonal and latitudinal variations of thermosphere composition (e.g., Jones et al., 2017 , 2014 ; Wu et al., 2017 ; Yamazaki & Richmond, 2013 ). For example, the lower thermospheric residual circulation reduces the summer‐to‐winter gradient of O/N 2 (Qian & Yue, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…The lower atmosphere can also contribute to the latitudinal dependency of the summer‐to‐winter difference in ∑ O/N 2 . Seasonal and latitudinal variations in wave/tidal activity, turbulent mixing, and residual circulations in the mesosphere and lower thermosphere region strongly impact the seasonal and latitudinal variations of thermosphere composition (e.g., Jones et al., 2017 , 2014 ; Wu et al., 2017 ; Yamazaki & Richmond, 2013 ). For example, the lower thermospheric residual circulation reduces the summer‐to‐winter gradient of O/N 2 (Qian & Yue, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…nO2+ ${n}_{{O}_{2}^{+}}$ decreases continuously for the entire 27‐day solar rotation period, which is also due to the accumulation of O + (decreased loss). Under realistic conditions, variations of the eddy diffusion are smaller (Salinas et al., 2016; Wu et al., 2017) and therefore a smaller influence on the delay is expected. The effect on the neutral components must also be considered when variations in eddy diffusion occur (Qian et al., 2009, 2013).…”
Section: Simulation Of the Height‐dependent Delayed Ionospheric Responsementioning
confidence: 99%
“…Recently, Wu et al (2017) showed that imposing the Qian et al (2009) IAVs in K zz in the TIE-GCM improved the model's capability of reproducing observed IAVs in electron density measured by the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) satellites. Analogous to the TIME-GCM results presented in Jones et al (2017), Wu et al (2017) demonstrated that tidal dissipation in the MLT region damps the ionospheric SAO in the TIE-GCM. Examination of both observed and modeled IAVs in TEC, N m F 2 , and electron density peak height (h m F 2 ) strongly suggests that the ionospheric SAO is largely driven in direct response to the SAO in thermospheric O/N 2 , as demonstrated by Rishbeth, Müller-Wodarg, et al (2000).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Rishbeth, Müller-Wodarg, et al (2000) expounded on the physical discussion of the TSM presented by Fuller-Rowell (1998) stating that IAVs in O/N 2 at low and middle latitudes driven by IAVs in the large-scale thermospheric meridional and vertical circulation directly forced an ionospheric SAO in the peak electron density (N m F 2 ). Recently, Wu et al (2017) showed that imposing the Qian et al (2009) IAVs in K zz in the TIE-GCM improved the model's capability of reproducing observed IAVs in electron density measured by the Constellation Observing System for Meteorology, Ionosphere, and Climate (COSMIC) satellites. Analogous to the TIME-GCM results presented in Jones et al (2017), Wu et al (2017) demonstrated that tidal dissipation in the MLT region damps the ionospheric SAO in the TIE-GCM.…”
mentioning
confidence: 99%